Evaluasi Program Penguatan Pendidikan Karakter (PPK) Berdasar Model Goal Free Pada Sekolah Dasar - Ika Rismawati; Bambang Ismanto (Kelola: Jurnal Manajemen Pendidikan, 2023)
Character education is essential for the life of a nation. The condition of the nation's character is alarming, marked by the number of bullying in schools, promiscuity, and increasing drug cases infecting school-age children. This can threaten the integrity of the Unitary State of the Republic of Indonesia. Therefore a special strategy is needed to shape the character of the nation's young generation. Character education is carried out in schools by being integrated into various activities at school. The implementation of the PPK program needs to be evaluated to find out all the things that happened during program implementation. The evaluation research conducted is program evaluation research. The evaluation model used is a goal-free evaluation model. Michael Scrieven developed the goal-free evaluation model. This evaluation model determines the planning, implementation, analysis, and follow-up of the character education strengthening program at Gugus Teuku Umar Salatiga. The planning stage of the character education supporting program at Gugus Teuku Umar has been carried out well. The character education strengthening program has been implemented in every activity in the school. The character education strengthening program implemented at Gugus Teuku Umar has a positive impact on student behavior and student achievement.1. The planning of the character education program at Gugus Teuku Umar from the planning stage has been carried out well. 2. The character education program has been implemented well but not yet to be optimal. 3. The stages of practical examination (check) have been carried out so that the implementation of the PPK program can influence the character education program to positively impact students both on behavior and attitudes as well as learning achievement. 4. 5. There has been a follow-up to implementing the PPK program in schools. This was done based on the results of the analysis. Programs with positive impacts will undoubtedly continue their implementation. Programs with more negative side effects will be updated or replaced with other programs.